A global design principle for polysulfide electrocatalysis in lithium–sulfur batteries—A computational perspective. Issue 3 (27th May 2022) - Abraham, Akhil M.; Boteju, Thilini; Ponnurangam, Sathish; Thangadurai, Venkataraman
Abstract: Widespread commercialization of high‐energy‐density lithium–sulfur (Li–S) batteries is difficult due to the lithium polysulfide, Li2 S n ( n = 4, 6, 8), shuttle effect. Efficient adsorption/conversion of Li2 S n species on an electrocatalytic surface can suppress the shuttle effect. Modeling of the adsorption of Li2 S n species using density functional theory (DFT) calculations has contributed significantly toward an understanding of their anchoring mechanism at a surface. Different surfaces show a unique range of binding energies for faster Li2 S n adsorption/reaction kinetics. To predict the optimum binding energy zone, a systematic DFT study is performed on transition‐metal sulfide (TMS) surfaces including TiS2, VS2, NbS2, MoS2, WS2, and SnS2 . The investigation revealed that the geometric properties at the anchoring site possibly regulate the adsorption energy of Li2 S n species. A geometry parameter, G score, is defined as a function of bond length and number of lithium‐atom interactions between the Li2 S n species and the binding surface. The design principle is extended to sulfur‐deficient (TMSs‐x) and edge‐exposed (TMS(100)) surfaces. The G score predicts the most effective binding energy zone distinctive to these materials—TMS (1.7–2.1 eV/ G score ≥ 2.0), TMSs‐x (2.0–2.8 eV/ G score ≥ 2.1), and TMS(100) (2.5–3.2 eV/Gscore ≥ 1.09). Abstract : Suppression of the polysulfide shuttle effect is crucial to achieve high‐energy‐density lithium–sulfur batteries. Finding an optimum adsorption energy distinct to a plane is critical for efficient adsorption and conversion of polysulfides. A density functional theory‐guided design principle is proposed to predict ideal adsorption energies unique to a surface.